Personal Assistants: Emerging Computational Technologies (Intelligent Systems Reference Library, 2018)
This book provides an overview of the current research in the interdisciplinary area of personal assistants (PA) and cognitively inspired systems. It discusses the most relevant topics in this highly diversified domain, like reasoning, health, personalization, robotics, and ethical and social issues. Personal assistants (PA) are a relatively new concept directed at people with cognitive or physical disabilities, and is expanding to include complex platforms such as sensors, actuators, monitoring abilities and decision processes. Designed for a general audience, it is also of interest to undergraduates, graduates and researchers involved with intelligent systems, ambient intelligence or ambient assisted living. The content goes from an introduction of the field (aimed at undergraduates and a general readership) to specific and complex architectures (aimed at graduates and researchers).